The effectiveness of sports-based counseling on the mental well-being of adolescents experiencing social anxiety - Hazima, Haura; Basuki, Agus (Universitas Tanjungpura, 2025)
Background. Social anxiety is one of the most common mental health problems experienced by adolescents and has the potential to hinder social functioning, academic performance, and overall mental well-being. Although conventional counseling has been proven effective in treating social anxiety, this approach generally does not integrate physical activity as part of the therapeutic process. Objectives. This study aims to examine the effectiveness of sports-based counseling in improving the mental well-being of adolescents with social anxiety. Methods. The study used a quasi-experimental design with a pretest–posttest control group model. Participants were adolescents aged 13–18 years with moderate to high levels of social anxiety, who were divided into an experimental group and a control group. The experimental group participated in a sports-based counseling program for 6–8 weeks, while the control group did not receive any structured sports intervention. Mental well-being and social anxiety were measured using validated psychometric instruments. Results. The results of the analysis showed that the experimental group experienced a significant increase in mental well-being compared to the control group, as well as a significant decrease in social anxiety levels after the intervention. These findings indicate that sports-based counseling is effective as an integrated psychosocial intervention in improving the mental well-being of adolescents with social anxiety. Conclusion. This study contributes theoretically to the development of the integration of sports psychology and developmental counseling, as well as practically to the development of applicable and contextual adolescent mental health intervention programs.